Child Sponsorship Exploring Pathways to a Brighter Future - Watson, B.; Clarke, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book reviews the remarkable growth, diversity and challenges of child sponsorship. It features the latest progress in child sponsorship practice and necessary tensions experienced by some organisations as they seek to maximise impact.
Keywords: International relations; Social work; Development economics; Economic development; Political communication; Social groups; Family; International Relations; Social Work; Development Economics; Development Studies; Political Communication; Sociology of Family, Youth and Aging